Pumice cone eruptions at Aluto volcano, Ethiopia - Clarke, Ben; Calder, Eliza S.; Fontijn, Karen; Desalegn, Firawalin; Tierz, Pablo; Yirgu, Gezahegn (Volcanica, 2024)
Pumice cones are volcanic landforms that exist worldwide, but whose eruption has never been observed. Interpretations of these eruptions vary significantly in style, intensity, and magnitude, pertinent for volcanic hazard assessment. Aluto volcano (Ethiopia) provides an unprecedented insight into the hazardous nature of these enigmatic eruptions. We investigate nine such pumice cones, and find that they are the product of moderate-intensity explosive eruptions that develop a sustained but unsteady eruption column, deposit lapilli- to block-sized tephra close to the vent forming pumice cones, can deposit distal tephra from an umbrella cloud, produce pyroclastic density currents by repeated partial column-collapse, and end with the emplacement of silicic lava. Like basaltic pyroclastic cones, pumice cones can also undergo collapse by lava flow emplacement. Alongside recent evaluation of distal tephras, we suggest that these eruptions, at least at Aluto, vary in intensity and magnitude from violent-Strombolian to sub-Plinian, and each follow a remarkably similar sequence of eruptive processes.